The influence of organizational culture towards the level of employees’ competency: a case study of Majlis Bandaraya Kuala Terengganu (MBKT) / Rashidah Mohd Ibrahim, Rosmimi Ramli and Ku Naraini Che Ku Yusof - Mohd Ibrahim, Rashidah; Ramli, Rosmimi; Che Ku Yusof, Ku Naraini (2008)
Majlis Bandaraya Kuala Terengganu (MBKT) is the 12th municipal council being inaugural the city council status on January 1st, 2008. MBKT’s main function is to provide efficient and effective urban services, to implement all development projects at the local community level and to ensure a conducive and safe environment for its residents, workers and visitors. The powers and functions of MBKT is governed by three main Acts namely, Town and Country Planning Act 1976, Local Government Act 1976 and Street, Drainage and Building Act 1974 besides many other by-laws that act as an enforcement authority. The aim of the research is to determine the influence of organizational culture on employees ’ competency. Theoretical framework is developed with three variables - organizational culture (independent variable) with three underlying components, namely involvement, consistency and adaptability; demographic (independent variable) with seven underlying components namely, gender, marital status, age, latest qualification, years in service, service group and salary and competency (dependent variable) with three underlying components namely, communication, planning and teamwork. Researchers have used survey method whereby through convenient sampling technique, 48 employees of the MBKT have been selected as sample